Archaeological Investigations at Striplands Farm West, Longstanton - Patten, Ricky (Cambridge Archaeological Unit, Department of Archaeology, University of Cambridge, 2004)
During September of 2004 an archaeological investigation was undertaken on behalf of Gallahers Ltd within the southern portion of Field H and a series of enclosures forming Field Q. The excavation of twenty-three trenches produced evidence for human activity spanning the Late Bronze Age/Iron Age through to the Saxo-Norman period. Late Bronze Age/Iron Age settlement was recorded in a series of trenches spanning Fields H and Q in the form of gullies and postholes and a large pit containing preserved organics. On an area of high ground Saxon settlement was envisioned in the form of a possible grubenhaus and associated linears, possibly relating to earlier settlement activity recorded to the west at Home Farm. Fronting onto the present course of the B1050 Saxo-Norman ditches were noted within two trenches in Field Q representing possible evidence for the early layout of the village of Longstanton.